2020
DOI: 10.3390/plants9111595
|View full text |Cite
|
Sign up to set email alerts
|

Canavanine Increases the Content of Phenolic Compounds in Tomato (Solanum lycopersicum L.) Roots

Abstract: Canavanine (CAN) is a nonproteinogenic amino acid, and its toxicity comes from its utilization instead of arginine in many cellular processes. As presented in previous experiments, supplementation of tomato (Solanum lycopersicum L.) with CAN led to decreased nitric oxide (NO) level and induced secondary oxidative stress. CAN improved total antioxidant capacity in roots, with parallel inhibition of enzymatic antioxidants. The aim of this work was to determine how CAN-dependent limitation of NO emission and reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Indeed, the analysis of the adsorption of Fe 3+ with ZIP indicated that the strongest adsorption occurs due to coordination interactions between Fe 3+ and the carboxyl groups of the peptide. This coordination interaction was visually represented in Figure S11D, highlighting the specific binding sites and the formation of coordination complexes between Fe 3+ ions and the carboxyl groups in ZIP . This coordination complex contributed to a stronger binding affinity and stability, making it more difficult for Fe 3+ to desorb from the ZIP surface compared to other ions.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, the analysis of the adsorption of Fe 3+ with ZIP indicated that the strongest adsorption occurs due to coordination interactions between Fe 3+ and the carboxyl groups of the peptide. This coordination interaction was visually represented in Figure S11D, highlighting the specific binding sites and the formation of coordination complexes between Fe 3+ ions and the carboxyl groups in ZIP . This coordination complex contributed to a stronger binding affinity and stability, making it more difficult for Fe 3+ to desorb from the ZIP surface compared to other ions.…”
Section: Resultsmentioning
confidence: 96%
“…This coordination interaction was visually represented in Figure S11D, highlighting the specific binding sites and the formation of coordination complexes between Fe 3+ ions and the carboxyl groups in ZIP. 20 This coordination complex contributed to a stronger binding affinity and stability, making it more difficult for Fe 3+ to desorb from the ZIP surface compared to other ions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The production of toxic canavanine is mainly limited to Fabaceae species. Seeds of Canavalia, Dioclea, Hedysarum, and Medicago sativa L. are rich in canavanine [156]. Some insect herbivores (e.g., Drosophila species) avoid feeding on plants containing canavanine, demonstrating its toxicity and repellent effects against insects [157].…”
Section: Smsmentioning
confidence: 99%
“…Furthermore, many of the known PCs can directly or indirectly interact with ROS. These endogenous growth regulators can chelate copper and iron ions and, thus, they are able to reduce free-radical formation due to the Fenton reaction [ 38 ].…”
Section: Introductionmentioning
confidence: 99%